6y+2=-2y+26

Simple and best practice solution for 6y+2=-2y+26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+2=-2y+26 equation:


Simplifying
6y + 2 = -2y + 26

Reorder the terms:
2 + 6y = -2y + 26

Reorder the terms:
2 + 6y = 26 + -2y

Solving
2 + 6y = 26 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
2 + 6y + 2y = 26 + -2y + 2y

Combine like terms: 6y + 2y = 8y
2 + 8y = 26 + -2y + 2y

Combine like terms: -2y + 2y = 0
2 + 8y = 26 + 0
2 + 8y = 26

Add '-2' to each side of the equation.
2 + -2 + 8y = 26 + -2

Combine like terms: 2 + -2 = 0
0 + 8y = 26 + -2
8y = 26 + -2

Combine like terms: 26 + -2 = 24
8y = 24

Divide each side by '8'.
y = 3

Simplifying
y = 3

See similar equations:

| 4v-10=54 | | y/6-3=4 | | -6n+16-3n+9=n-40 | | r/14=13 | | 5m-4=2m+23 | | 5/7x=105 | | r^2+8r-0=20 | | d+118=907 | | 85x-4-9x=18+76x-22 | | 5/9(86-32) | | -4x+8x-5=4(x-1)-17 | | 71.43x=105 | | 3k+9=30 | | 4(y-5)+2=5 | | 3(3x+9)=9-2(x-9) | | 21p=819 | | s=bd-9 | | r/11=20 | | 3/8-5/15 | | 2c+8=-10c | | y=2x+45 | | 23-5x=32 | | 6-9x=7x+8 | | 3(5+x)=3 | | 88-1/3x9 | | 24=s/-22 | | 4-x-3x=-8 | | 3/4w-12w-4=12 | | 2x-4(3-2x)=4(x-5)-28 | | 150w+2=195w+1 | | 432=27v | | 6y/2y |

Equations solver categories